Breast Cancer Status in The Northern Part of West Bank - Ahmad Z. Haj-Qasem (My University, 2000)
The current study is an explorative and descriptive in nature. It aimed to study the status of breast cancer in northern part of the West Bank and compare it with the other parts of the area. We also aimed to evaluate the risk factors associated with the disease incidence. Previous studies on breast cancer in Palestine, Jordan and Israel were revised. The study also included all affected women (80) enrolled at Al-Watani cancer center in northern part of West Bank at the city of Nablus. The affected women were interviewed and their medical tiles were studied. Our findings indicate rapid increase in breast cancer incidence in West Bank in comparison with the situation among Israeli women, although the disease incidence among Jewish females is the highest. There is a geographical variation in the incidence of the disease in West Bank. These variations seem to be due to life style, socio-economical and health awareness of affected women. Our findings strongly indicate the lack of health awareness among females in this respect. Our findings also indicate that lactation, being married and having children especially at early age seems to play a protective role against breast cancer. On the other hand, smoking, oral contraceptive use specially at early age, stress, low fertility, early menarche and family history seem to play a role in the disease etiology and its incidence at early age of breast cancer.

هذه الدراسة وصفية هدفت إلى التعرف على وضع سرطان الثدي في الضفة الغربية خاصة في منطقة الشمال ومقارنته مع كل من الأردن وإسرائيل. كما هدفت هذه الدراسة إلى التعرف على عوامل الخطورة التي من الممكن أن تتسبب المرض. من أجل ذلك تمت مراجعة الدراسات والأبحاث السابقة عن المرض في الأردن وإسرائيل وفلسطين. وتم كذلك مقابلة 80 مريضة سرطان من اصل 125 حالة تم تشخصيها في السنوات الثلاث الاخيرة في شمال الضفة الغربية كما تمت دراسة الملفات الطبية الخاصة بهم. لوحظ أن الإصابة بسرطان الثدي تزداد بشكل كبير بين النساء العربيات مقارنة باليهوديات على الرغم من أن معدلات الإصابة لدى اليهوديات أعلى منها عند الفلسطينيات. ولوحظ كذلك وجود اختلاف في معدلات الإصابة بين المناطق المختلفة في الضفة قد يكون السبب فيها اختلاف في طبيعة الحياة والظروف الاقتصادية والاجتماعية والوعي الصحي. وكما أظهرت نتائج هذه الدراسة أن الإرضاع والانجاب قبل سن الثلاثين يلعبان دوراً وقائيا من الإصابة بسرطان الثدي. ومن جهة أخرى كان للتدخين وانخفاض معدلات الخصوبة والتوتر وحبوب منع الحمل والبلوغ المبكر وكذلك التاريخ العائلي للمرض دورا في الإصابة بالمرض.
Breast Cancer Status in The Northern Part of West Bank